Combined Oral Contraceptive Pill Induced Hypertension and Hypertensive Disorders of Pregnancy: Shared Mechanisms and Clinical Similarities - Gunaratne, Madugodaralalage D. S. K. (Curr Hypertens Rep, 2021)
PURPOSE OF REVIEW: Oral contraceptive pill induced hypertension (OCPIH) and hypertensive disorders in pregnancy (HDP) share common risk factors and pathophysiological mechanisms, yet the bidirectional relationship between these two conditions is not well-established. We review and describe OCPIH and HDP to better understand how hormonal and metabolic imbalances affect hypertension. RECENT FINDINGS: Oral contraceptive pills continue to be a popular method of contraception, with an incidence of OCPIH ranging from 1%−8.5% among OCP users. HDP have an incidence of 5–10% of all pregnancies in the United States and have been shown to be a powerful predictor of lifetime adverse cardiovascular outcomes, including future hypertension. OCPIH and HDP share common risk factors such as age, BMI, past personal and family history of hypertension, as well as pathogenic mechanisms, including alterations in hormonal metabolism and the renin angiotensin aldosterone system; imbalance of vasodilator – vasoconstrictor compounds; and changes in the cardiovascular system. SUMMARY: Future research should address additional potential mechanisms that underlie hypertension in these two conditions where endocrine changes, either physiological (pregnancy) or iatrogenic (use of OCP), play a role. This may lead to novel, targeted treatment options to improve hypertension management and overall cardiovascular risk profile management in this subset of young female patients.